A COMPARATIVE STUDY ON THE KINDS OF WEEDS OF PALM PLANTATIONS IN TABUK AND AL-QASSIM REGIONS IN SAUDI ARABIA - Al-Harbi, N. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate weeds kind in palm plantations. Date palm is the most chief economic crop in most countries of the Arabian Peninsula. Many factors, such as the presence of weeds, may cause a huge loss in the production of dates. Despite the severe damage caused by the presence of some weeds in agroecosystems, many weeds have many medicinal and economic uses. A total of 62 species were listed in palm Plantations in Tabuk and Al-Qassim Regions. A total of 51 species were listed in Tabuk Region (The number of unique species in the Tabuk Region reached 32 that not recorded in Al-Qassim Region. Also, 19 species were recorded in both of Tabuk and Al-Qassim Regions). A total of 30 weeds were listed in Al-Qassim Region (The number of unique species in the Al-Qassim Region reached 11 that not recorded in the Tabuk Region. In addition to, 19 species were recorded in both of Tabuk and Al-Qassim Regions). Zygophyllaceae was the most common family, the majority life span was annuals and the most common life form was therophyte in both Tabuk and Al-Qassim Regions. Data management and classification were achieved using PCORD (TWINSPAN and DCA analyses).